Exciterless solutions for medium-power wound-field synchronous generators - Fallows, Daniel James Alfred (2022)
Exciterless solutions offer many benefits to the wound-field synchronous machine designer, most prominent of which is the significant potential increase in power density. Yet, whilst many topologies have been proposed, they exist only for low power machines and little previous work has been done for higher power units. Instead, the AC exciter remains the system of choice despite its disadvantages. This work investigates the scalability of existing exciterless topologies to larger machines, within the confines of minimising manufacturing changes. Through this, two new excitation topologies are developed, one of which provides an exciterless solution without any change to the main generator magnetic design. A functional prototype has been developed and validated, providing a full proof-of-concept for this methodology. The exciterless topology demonstrated in this work, along with the modelling and optimisation methodology used, provides a template for machine designers to rapidly update existing generator designs; finally unlocking the benefits of exciterless.